IL‐31 transgenic mice show reduced allergen‐induced lung inflammation - Neuper, Theresa; Neureiter, Daniel; Sarajlic, Muamera; Strandt, Helen; Bauer, Renate; Schwarz, Harald; Suchanek, Patrick; Korotchenko, Evgeniia; Dillon, Stacey R.; Hammerl, Peter; Stoecklinger, Angelika; Weiss, Richard; et al. (European journal of immunology, 2021)
Interleukin‐31 (IL‐31) is a Th2 cell–derived cytokine that has been closely linked to pruritic skin inflammation. More recently, enhanced IL‐31 serum levels have also been observed in patients with allergic rhinitis and allergic asthma. Therefore, the main aim of this study was to unravel the contribution of IL‐31 to allergen‐induced lung inflammation. We analyzed lung inflammation in response to the timothy grass (Phleum pratense) pollen allergen Phl p 5 in C57BL/6 wild‐type (wt) mice, IL‐31 transgenic (IL‐31tg) mice, and IL‐31 receptor alpha‐deficient animals (IL‐31RA−/−). IL‐31 and IL‐31RA levels were monitored by qRT‐PCR. Cellular infiltrate in bronchoalveolar lavage fluid (BALF) and lung tissue inflammation, mucus production as well as epithelial thickness were measured by flow cytometry and histomorphology. While allergen challenge induced IL‐31RA expression in lung tissue of wt and IL‐31tg mice, high IL‐31 expression was exclusively observed in lung tissue of IL‐31tg mice. Upon Phl p 5 challenge, IL‐31tg mice showed reduced numbers of leukocytes and eosinophils in BALF and lung tissue as well as diminished mucin expression and less pronounced epithelial thickening compared to IL‐31RA−/− or wt animals. These findings suggest that the IL‐31/IL‐31RA axis may regulate local, allergen‐induced inflammation in the lungs. This study describes a role for IL‐31 signaling in the context of allergen‐induced lung inflammation. Mice overexpressing IL‐31 develop less severe lung inflammation upon allergen exposure, characterized by decreased leukocyte infiltration, mucus production and epithelial thickening. Thus, our data indicate that IL‐31 signaling regulates allergen‐induced lung inflammation.